The efficacy of antioxidants in sperm parameters and production of reactive oxygen species levels during the freeze‐thaw process: A systematic review and meta‐analysis. (21st January 2020) - Bahmyari, Rezvan; Zare, Morteza; Sharma, Rakesh; Agarwal, Ashok; Halvaei, Iman
Abstract: To investigate the impact of antioxidants in sperm parameters and reduction in reactive oxygen species production during the freeze‐thaw process. PubMed, Scopus, Web of Science, Embase and Cochrane central library were systematically searched. Of the 1583 articles, 23 studies were selected for data extraction. Our results show that antioxidants improved sperm progressive motility (standardised mean difference (SMD) = 1; 95% CI: 0.62, 1.38; p < .001) and viability (SMD = 1.20; 95% CI: 0.50, 1.91; p = .001) and reduced sperm DNA fragmentation (SDF) and hydrogen peroxide (H2 O2 ) production, but there was no significant improvement in total sperm motility after thawing. Acetyl‐l‐carnitine/l‐carnitine, melatonin and catalase had a significant positive impact on progressive motility. The role of tempol and melatonin in improving viability was significant compared to other antioxidants. Moreover, a significant reduction in SDF was observed after addition of butylated hydroxytoluene, tempol and vitamin E. However, the prevention of H2 O2 production was significant only after the addition of tempol. Our overall results displayed the positive impact of antioxidants on progressive sperm motility, viability and reduction in SDF and H2 O2 production, but no significant impact of antioxidants on total sperm motility was seen during the freeze‐thaw process.